MATERNAL FACTORS ASSOCIATED WITH INTRAUTERINE GROWTH RESTRICTION - Muhammad, Taj; Khattak, Asmat Ara; Rehman, Shafiq -ur-; Khan, Muhammad Amjad; Khan, Afzal; Khan, Muhammad Aqeel (Journal of Ayub Medical College Abbottabad, 2010)
Background: Intrauterine growth restriction is a major neonatal health issue. Maternal factors have been found to have greater impact on IUGR. Studying these factors can help in reducing the mortality and morbidity associated with IUGR. Methods: This Case-control study was conducted at the department of Paediatrics Post-graduate medical institute Lady Reading Hospital Peshawar from March 2008-April 2009. Small-for-gestational age (SGA, i.e., IUGR cases and n=200) live born babies were compared with appropriate-for-gestational age (AGA, i.e., controls and n=200) babies. Information regarding socio-demographics of mothers, gestational age and birth weight of baby, maternal clinical characteristics, and medical and obstetric complications during pregnancy was recorded on a predesigned proforma. Data analysis was done through SPSS-16. To find the maternal factors associated with the intrauterine growth restriction, multivariable logistic regression was used. We also did two different sets of logistic regression analysis for Symmetric and Asymmetric SGA babies as Cases. Results: After adjusting for other variables in the multivariable model we found that the mothers of IUGR babies were of younger age (OR=0.8, CI=0.7-0.9), were poor (OR=2.5, CI=1.4-4.4) and underweight (OR=3.5, CI=1.1-5.7) and had anaemia (OR=2.7, CI=1.3-5.4) in the index pregnancy, and had history of Previous IUGR birth (OR=9.7, CI=3.3-18.3) and placenta previa (OR=3.2, CI=1.1- 6.6). There was an interaction between pregnancy induced hypertension and parity of mother with a primary-para mother with pregnancy induced hypertension (PIH) having an increased risk for IUGR babies (OR=10.1, CI=1.0-23.2). Conclusion:. The studied factors need special attention in hospital based settings in order to improve the perinatal outcome in IUGR babies. Keywords: intrauterine growth restriction, pregnancy induced hypertension, maternal malnutrition, anaemia